CHILD GROOMING IN THE QUR’ANIC PERSPECTIVE: AN ANALYSIS OF CHILD PROTECTION IN THE DIGITAL AGE - Lailatus Syafa'ah; Mohammad Nabiel; Alfet Robi' Nur Muhammad; Muh Imam Sanusi Al Khanafi (Hikami : Jurnal Ilmu Alquran dan Tafsir, 2026)
The increasing prevalence of child grooming in digital spaces represents a new form of sexual violence against children that is covert, manipulative, and sustained over time. Private digital interactions with minimal supervision significantly heighten children’s vulnerability to psychological and emotional exploitation. While child protection has been widely examined in legal and psychological studies, Islamic scholarship that systematically explores Qur’anic-based child protection through a thematic tafsir approach remains limited. This study aims to: (1) formulate the concept of child protection in the Qur’an based on its foundational values and principles; (2) analyze child grooming practices through a Qur’anic ethical framework with reference to publicly documented digital cases; and (3) assess the relevance and actualization of these principles within increasingly complex digital interactions. Employing a qualitative library-based methodology, this research applies a thematic tafsir approach supported by linguistic and semantic analysis of key Qur’anic terms such as hifz (protection), zulm (injustice), and fasad (corruption). The findings demonstrate that the Qur’an positions children as moral and social subjects of protection; child grooming constitutes a form of zulm due to the abuse of power relations and fasad due to its destructive impact on children’s psychological development and social order; and Qur’anic principles remain ethically relevant and adaptable as preventive foundations for child protection in the digital era.